De novo Transcriptome Analysis Revealed Genes Involved in Flavonoid and Vitamin C Biosynthesis in Phyllanthus emblica (L.) - Kumar, Avneesh; Kumar, Sunil; Bains, Savita; Vaidya, Vanya; Singh, Baljinder; Kaur, Ravneet; Kaur, Jagdeep; Singh, Kashmir (Frontiers in Plant Science, 2016)
Phyllanthus emblica is an affluent source of various therapeutic components. A few of them like vitamin C and flavonoids are predominant bioactive compounds that are being used in immense pharmacological applications. In-spite of numerous applications, the genomic information of this plant was limited to a few expressed sequence tags (ESTs) in DNA databases. Herein, we developed in-depth transcriptome information of P. emblica using Illumina Hiseq 2000 platform and characterized. A total of 31,285,965 high-quality reads were assembled into 91,288 contigs with the N50 value 358. Out of them, 47,267 contigs were functionally annotated using BLASTX search against NCBI-non-redundant (NR) protein database. Further, 31,366 contigs showed similarity with various gene ontology (GO) terms, and 1,299 were related to different enzymes and biosynthetic pathways. We identified the transcripts related to each gene involved in flavonoid and vitamin C biosynthesis. Several cytochrome P450s (CYPs) and glucosyltransferases (GTs) genes involved in flavonoid biosynthesis and various other metabolic pathways were also documented. Further, 6510 transcription factors and 4420 EST derived simple sequence repeat (SSR) markers were also predicted. The present study enlightened various characteristic features of P. emblica genome, and provided an important resource for future molecular and functional genomics studies.